2017
DOI: 10.1128/aem.02799-16
|View full text |Cite
|
Sign up to set email alerts
|

White Syndrome-Affected Corals Have a Distinct Microbiome at Disease Lesion Fronts

Abstract: Coral tissue loss diseases, collectively known as white syndromes (WSs), induce significant mortality on reefs throughout the Indo-Pacific, yet definitive confirmation of WS etiologies remains elusive. In this study, we integrated ecological disease monitoring, bacterial community profiling, in situ visualization of microbehost interactions, and cellular responses of the host coral through an 18-month repeated-sampling regime. We assert that the observed pathogenesis of WS lesions on acroporid corals at Lizard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 59 publications
4
33
0
Order By: Relevance
“…A similar pattern is seen in freshwater microcystic blooms, on the first day Rhizobiales are one of the most abundant bacteria orders and after 2-4 days Rhizobiales decrease and Rhodobacterales become one of the most abundant orders (Li et al, 2011). Rhodobacterales are associated with multiple coral diseases, and this may not be because they are causative agents of disease, but rather they may be efficient successors and readily colonize diseased corals (Pollock et al, 2017). For example, corals inoculated with the known coral pathogen Vibrio coralliilyticus showed that initial timepoints had high relative abundances of Vibrionales, but hours later the relative abundances of Vibrionales decreased and relative abundances of Rhodobacterales increased (Welsh et al, 2017).…”
Section: Sctld Microbial Signatures In Lesions Of Four Diseased Coralmentioning
confidence: 58%
See 2 more Smart Citations
“…A similar pattern is seen in freshwater microcystic blooms, on the first day Rhizobiales are one of the most abundant bacteria orders and after 2-4 days Rhizobiales decrease and Rhodobacterales become one of the most abundant orders (Li et al, 2011). Rhodobacterales are associated with multiple coral diseases, and this may not be because they are causative agents of disease, but rather they may be efficient successors and readily colonize diseased corals (Pollock et al, 2017). For example, corals inoculated with the known coral pathogen Vibrio coralliilyticus showed that initial timepoints had high relative abundances of Vibrionales, but hours later the relative abundances of Vibrionales decreased and relative abundances of Rhodobacterales increased (Welsh et al, 2017).…”
Section: Sctld Microbial Signatures In Lesions Of Four Diseased Coralmentioning
confidence: 58%
“…AH SINT from the vulnerable zone had different bacteria enriched compared with the endemic and epidemic zones (Figure 4D). Unlike in the vulnerable zone, AH SINT in the endemic and epidemic zones had three bacterial taxa that have been linked to coral diseases -including SCTLD: Cryomorphaceae (Gignoux-Wolfsohn et al, 2017;Meyer et al, 2019), Rhizobiaceae (Cárdenas et al, 2012;Meyer et al, 2019), and Rhodobacteraceae (Sunagawa et al, 2009;Cárdenas et al, 2012;Roder et al, 2014;Gignoux-Wolfsohn et al, 2017;Pollock et al, 2017;Meyer et al, 2019) (Figure 4D). Although AH colonies of the other two coral species also grouped by zones, colonies sampled in the epidemic and endemic zones did not show any signatures that would suggest that they were exposed to disease (Figures 4E,F).…”
Section: Apparently Healthy Corals In Vulnerable Endemic and Epidemmentioning
confidence: 99%
See 1 more Smart Citation
“…This term has been introduced as a growing number of studies (not limited to coral), demonstrate shifts in the consortia of microbial communities linked with gross signs of compromised host health, rather than pointing at a single causative agent (reviewed in Vayssier‐Taussat et al ., ). Certain bacterial groups become more dominant in the pathobiome due to the complex interactions between environmental stress and the coral host (Pollock et al ., ; Vega Thurber et al ., ). In addition, it has been suggested recently that there is a ubiquitous core microbiome associated with corals that are likely beneficial to host health, together with the functional niche fillers and other highly variable microbial community members (Ainsworth et al ., ; Hernandez‐Agreda et al ., ; Peixoto et al ., ).…”
Section: Approaches To Understanding the Role Of Microorganisms In Comentioning
confidence: 99%
“…However, these traditional approaches have been argued to be challenging especially when applied to corals (for review see Richardson, 1998) and not suitable for polymicrobial diseases or microbial agents that cannot be cultured (Sato et al, 2016). Culture-independent molecular profiling of microbial communities targeting 16S rRNA gene sequences have also been extensively applied to disease lesions, to identify the microbial community composition associated with the diseased corals and directly compare them to healthy tissues (e.g., Cr oquer et al, 2013;Frias-lopez et al, 2004;Kimes et al, 2010;Meyer et al, 2014;Pantos and Bythell, 2006;Pollock et al, 2017;Soffer et al, 2015;Sunagawa et al, 2009). In some cases, causation has been inferred based on retrieval of sequences affiliated with previously characterized pathogens.…”
Section: Approaches To Understanding the Role Of Microorganisms In Comentioning
confidence: 99%